An updated meta-analysis of cardiac resynchronization therapy with or without defibrillation in patients with nonischemic cardiomyopathy - Liu, Fuwei; Gao, Xin; Luo, Jun (Frontiers in Cardiovascular Medicine, 2023)
Background Cardiac resynchronization therapy (CRT) is a major device therapy used to treat patients suffering from heart failure (HF) and electrical asynchrony. It can improve HF symptoms, reduce HF hospitalization time, and improve long-term survival in HF with and without implantable cardioverter (ICD) therapy. However, the benefit of defibrillator therapy in CRT-eligible patients with nonischemic cardiomyopathy (NICM) remains unknown. As a result, we conducted a systematic review and meta-analysis to compare clinical outcomes in patients with NICM and HF who were treated with implantable CRT defibrillators (CRT-D) vs. a CRT pacemaker (CRT-P) alone. Methods We searched the electronic databases PubMed, Embase, and Cochrane for all studies comparing CRT-D vs. CRT-P treatment in patients with NICM. The time frame was from 1990 to September 2022. All-cause mortality and cardiovascular mortality were the primary clinical outcomes of interest to us. To pool adjusted hazard ratios (HRs) and 95% confidence intervals (CIs), a random-effects model with inverse variance was used. Results A pooled meta-analysis included two randomized controlled trials (RCTs), each with 1,200 CRT-eligible patients with NICM (592 with CRT-D and 608 with CRT-P) and nine cohort studies representing 27,568 CRT-eligible patients with NICM (16,196 with CRT-D and 11,372 with CRT-P). The adjusted HR for all-cause mortality for CRT-D vs. CRT-P was 0.90 (95% CI, 0.81-0.99). In a subgroup analysis of two RCTs and nine cohort studies, the adjusted HR for all-cause mortality was 0.72 (95% CI, 0.43–1.19) and HR 0.92 (95% CI, 0.83–1.03) for CRT-D vs. CRT-P, respectively. Conclusion With the addition of defibrillation leads, we found a significantly lower risk of all-cause mortality in patients with NICM, but this association was not found in subgroup analyses of RCTs and observational studies.